Black pioneers : an untold story - Katz, William Loren (New York : Atheneum Books for Young Readers, 1999)
A biographical history of influential African American pioneers and freedom fighters in the Midwest, including Sara Jane Woodson, Peter Clark, and Dred Scott.
Introduction : The Northwest Territory -- Black pathfinders and native Americans -- War, race, and slavery in the Ohio Valley -- Pioneer farmers of the Ohio Valley -- The determination of Sarah Jane Woodson -- Peter H. Clark's Cincinnati -- A railroad's "fierce passions" -- The Malvins of Cleveland -- The fight for liberty in Indiana -- "Warfare and strife" in Illinois -- The "Order of the men of oppression" -- The Iowa of Alexander Clark -- Wisconsin battles "The heel of oppression" -- The Greys of Minnisota -- From Missouri to Kansas : the odyssey of Henry Clay Bruce -- From "alien and stranger" to U.S. Army officer.
Includes bibliographical references (p. 179-181) and index.
Keywords: African American pioneers -- Middle West -- History -- Young adult literature; African American abolitionists -- Middle West -- History; African American pioneers -- Middle West -- Biography; African American abolitionists -- Middle West -- Biography; Middle West -- Race relations